If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1y + 8 = -6y + 3 Reorder the terms: 8 + -1y = -6y + 3 Reorder the terms: 8 + -1y = 3 + -6y Solving 8 + -1y = 3 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 8 + -1y + 6y = 3 + -6y + 6y Combine like terms: -1y + 6y = 5y 8 + 5y = 3 + -6y + 6y Combine like terms: -6y + 6y = 0 8 + 5y = 3 + 0 8 + 5y = 3 Add '-8' to each side of the equation. 8 + -8 + 5y = 3 + -8 Combine like terms: 8 + -8 = 0 0 + 5y = 3 + -8 5y = 3 + -8 Combine like terms: 3 + -8 = -5 5y = -5 Divide each side by '5'. y = -1 Simplifying y = -1
| n/15=13 | | 7x-4x=-12 | | C=24n+35 | | x-9=8x+11 | | 58+11=87- | | 80-x+145=135 | | x^7+3x^5-16x^3=0 | | 2.5=w-3.2 | | -2(2u-4)+6u=5+4(5u-3) | | 0.7z+1.9+0.12=5.5-0.4z | | .99x+19.95+65.35=144.67 | | x-x-40=180 | | 4x-20=180 | | 8x-4y+6=0 | | x+x-40=180 | | 5t/9=1/2 | | 6(-3)+4(5)= | | 11y=8y-x | | 2(x-4)=5-3(3x+1) | | 2(3.14)+d=5(3.14) | | -3-6(-4b-8)=11-4b | | 3x-(5-2x)=9x+3 | | y+11=19-4y | | 2r-(5-r)=13+3r | | x+x-180=180 | | 5+3x=(x+3) | | a-2.5=4.5 | | -5w-7=5w-7 | | 4r+4= | | -2=-3-e | | 5x+3=3+7x-8 | | -3.3q-4.4-5.5q=-3.2q-1.9 |